Genome-wide gene expression of a natural hybrid between Saccharomyces cerevisiae and S. kudriavzevii under enological conditions - Combina, Mariana; Perez Torrado, Roberto; Tronchoni, Jordi; Belloch, Carmela; Querol, Amparo (Elsevier, 2019)
The species Saccharomyces cerevisiae plays a predominant role in the wine making process. However, other species have been associated with must fermentation, such as Saccharomyces uvarum (Saccharomyces bayanus var. uvarum) or Saccharomyces paradoxus. Recently, yeast hybrids of different Saccharomyces species have also been reported as responsible for wine production. Yeast hybrids between the species S. cerevisiae × S. kudriavzevii isolated in wine fermentations show enhanced performance in low temperature enological conditions and increased production of interesting aroma compounds. In this work, we have studied the transcriptomic response in enological conditions of a S. cerevisiae × S. kudriavzevii hybrid strain and compared it with the reference species of S. cerevisiae and S. kudriavzevii. The results show that the hybrid strain presents an up-regulation of genes belonging to functional group translation and amino-acid metabolism. Moreover, key genes related to cold stress and production of glycerol and aroma compounds were also up-regulated. While some genes inherited regulation patterns from one of the parents, most of the up-regulated genes presented a new gene expression pattern, probably generated during the hybridization and adaptation process.